Tropospheric O3 Model from Climatological Approaches in the Colombian Andes (2021)
We identified two climatological parameters that are key to modeling the behavior of tropospheric ozone (O3) produced in the urban area of a heavily polluted city in the Colombian Andes. These parameters are the relative humidity (RH) and total radiation intensity (I). In topographically constrained areas, the production of tropospheric O3, as a by-product during photo-oxidation of carbon monoxide (CO) and nitrogen oxides (NO and NO2) has received much attention over the last decades. Models used to describe O3 dynamics are based on computationally demanding techniques that require lots of input data, however. This study proposes a simple approach for describing O3. To that end, it evaluates fifteen empirical models based on the combination of four linear regressions: O3 against RH, temperature (T), wind speed (U), and I. Each model is driven by the analyzed climatological parameters over the period from 2012 to 2018 and further run using either daily or monthly averaged data. The best fitting model for monthly averaged data outperformed that for daily averaged data in both mathematical simplicity and accuracy; however, the differences between these models remained <0.4 percent. The results suggest that the O3 produced increases with I and decreases with RH.